2012
DOI: 10.1021/ol303036j
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Nostodione A, a Cyanobacterial Metabolite

Abstract: The first total synthesis of the mitotic spindle poison nostodione A is described. The inherent oxidative sensitivity of indoles is utilized for a late introduction of a second carbonyl to the cyclopent[b]indole-2-one system. The tricyclic system is prepared from indole-3-acetic acid and O-silylated 4-ethynylphenol, using a stereoselective intramolecular reductive Heck cyclization as the key transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…HMBC data: H-9 to C-1, C-2a, C-11; H-11/15 to C-9, C-14; H-7 to C-5, C-3a; H-4 to C-6, C-3a, C-7a. These spectroscopic data were suitable with those reported in the literature [9].…”
Section: Extraction and Isolationsupporting
confidence: 89%
“…HMBC data: H-9 to C-1, C-2a, C-11; H-11/15 to C-9, C-14; H-7 to C-5, C-3a; H-4 to C-6, C-3a, C-7a. These spectroscopic data were suitable with those reported in the literature [9].…”
Section: Extraction and Isolationsupporting
confidence: 89%
“…Ekebergh et al. reported the total synthesis of nostodione A alkaloid . Alcohol 8 upon subjection to standard reductive Heck conditions employing Pd‐catalyst and formic acid as reductant gave the desired allylic alcohol 9 (Scheme ).…”
Section: Intramolecular Approachmentioning
confidence: 99%
“…Ekebergh et al reported the total synthesis of nostodione A alkaloid. [26] Alcohol 8 upon subjection to standard reductive Heck conditions employing Pd-catalyst and formic acid as reductant gave the desired allylic alcohol 9 (Scheme 2). Further Oppenauer type oxidation of allylic alcohol 9 utilizing the ruthenium based Shvo catalyst furnished β-unsaturated ketone compound which transformed to the nostodione A 10 via two steps namely Yonemitsu oxidation protocol and fluoride ion based sillyl excision.…”
Section: Formation Of Carbon Cyclementioning
confidence: 99%
“…[3][4][5] These oxygenic photoautotrophic prokaryotes, commonly referred to as blue-green algae, date back as far as 3.5 billion years 6 and adopt filamentous, unicellular, or aggregated morphologies generally reflective of the habitats to which they have adapted. [7][8] From those alkaloids reported in the last few decades, members of the classes of hapalindoles, 9-21 fischerindoles, 9,[17][18]22 ambiguines, 23,[36][37] and welwitindolinones 9,18,22,[25][26][27][28][29] have received significant attention from the synthetic community, with over 10 groups rendering total or formal protocols -many with enantioselective precision -since their first isolation in 1984. 30 The sunscreen indole pigments scytonemin (1), 31 nostodione A (2), [32][33][34] and prenostodione (3), 33 isolated from a variety of cyanobacterial species including Scytonema sp., Nostoc sp., and Scytonema hofmanni, however, have not garnered the same level of interest.…”
Section: Introductionmentioning
confidence: 99%
“…30 The sunscreen indole pigments scytonemin (1), 31 nostodione A (2), [32][33][34] and prenostodione (3), 33 isolated from a variety of cyanobacterial species including Scytonema sp., Nostoc sp., and Scytonema hofmanni, however, have not garnered the same level of interest. While a few total syntheses of these three species are available, [35][36][37][38][39] the focus has been on the exploration of their bioactivity and their enzymatically determined biosynthetic pathways. [40][41][42][43][44][45][46][47][48] More interestingly, the syntheses of four recently isolated and structurally-related derivatives -scytonine (4), dimethoxyscytonemin (5), tetramethoxyscytonemin (6), 49 and scytonemin-3a-imine (7) 50 -remain unreported (Figure 1).…”
Section: Introductionmentioning
confidence: 99%